Ethnicity, job search and labor market reintegration of the unemployed - Amelie F. Constant; Martin Kahanec; Ulf Rinne; Klaus F. Zimmermann (Institute for the Study of Labor (IZA), 2009)
This paper is based on recently collected and rich survey data of a representative sample of entrants into unemployment in Germany. Our data include a large number of migration variables, allowing us to adapt a recently developed concept of ethnic identity: the ethnosizer. To shed further light on the native-migrant differences in economic outcomes, we investigate the labor market reintegration, patterns of job search, and reservation wages across unemployed migrants and natives in Germany. Our results indicate that separated migrants have a relatively slow reintegration into the labor market. We explain this finding by arguing that this group exerts a relatively low search effort and that it has reservation wages which are moderate, yet still above the level which would imply similar employment probabilities as other groups of migrants.
Keywords: F22; J15; J61; J64; 330; Migration; ethnicity; ethnic identity; ethnosizer; unemployment; job search; reservation wages; Arbeitslosigkeit; Migranten; Kulturpsychologie; Berufliche Integration; Arbeitsuche; Anspruchslohn; Deutschland